The respiratory effects of chloramine-T exposure in seawater acclimated and amoebic gill disease-affected Atlantic salmon Salmo salar L - Melanie Leef; Harris, JO; Powell, MD (2007)
The aim of the present study was to examine the respiratory effects of chloramine-T, a proposed novel chemotherapeutic treatment for seawater-acclimated Atlantic salmon Salmo salar (L.) affected by amoebic gill disease (AGD). Following a surgical recovery period of 20-24Â h, fish, both healthy (N = 21) and AGD-affected (N = 13) were exposed to either a 1-hour pulse of seawater containing chloramine-T at a therapeutic concentration of 10Â mg L - 1 (experimental), or 100Â ml of sterile seawater (sham-treated controls). Arterial blood samples were repeatedly taken from a dorsal aortic catheter prior to exposure (0Â h), immediately following exposure (1Â h) and then at 3, 6, 12 and 24Â h and various respiratory parameters measured. Results showed that there were no significant effects relating to chloramine-T exposure regardless of disease status. Additional examination of the pH-bicarbonate diagrams confirmed that there was minimal acid-base disturbance in fish exposed to chloramine-T regardless of disease status. Significant changes seen within the examined haematological parameters of both healthy and AGD-affected fish appeared to be related to the repeated withdrawal of blood for analysis of respiratory parameters. Overall these results suggest that the use of chloramine-T in full-strength seawater at the therapeutic concentration of 10Â mg L - 1 for 1Â h had no significant respiratory effect in healthy or AGD-affected Atlantic salmon. Additionally, these results help to highlight the potential beneficial use of chloramine-T as a commercial treatment for gill diseased in marine Atlantic salmon. Â© 2007.